Effects of Brain Gymnastics on Decreased Stress Levels in College Students - Sri Sartini; Amirullah; Aszrul AB (Comprehensive Health Care, 2021)
The background of this study is non-pharmacological management to reduce stress one of which is brain gymnastics. Brain gymnastic movements can activate the neocortex and sympathetic nerves to reduce the increased production of adrenaline hormones in the body that can relieve psychological tension as well as physical tension. The purpose of this study is to find out the effect of brain gymnastics on the decrease in stress levels in students of the final level of the DIII Health Analyst Stikes Panrita Husada Bulukumba in 2019. The method used in this research using a pre-experiment research design with the one-group pre-post test design method. Sampling by means of Nonprobability sampling: Consecutive sampling with a total of 28 respondents. Measurement of stress levels using a watershed questionnaire (Depression Anxiety Stress Scale) with statistical tests used is a paired t-test. The results of this study showed that there was an effect of brain gymnastics exercise on the decrease in stress levels in students of the final level of the DIII Health Analyst Stikes Panrita Husada Bulukumba with a mean Pretest score of 22.61 while the mean Postest 12.75 so that the average value of changes in pretest and posttest stress levels with a mean value of 9,857 with an std. deviation of 3,354. In conclusion, there is a meaningful influence on brain gymnastics training on the decrease in stress levels in students of the final level of the DIII Health Analyst Stikes Panrita Husada Bulukumba 2019.